2017
DOI: 10.7567/jjap.57.011501
|View full text |Cite
|
Sign up to set email alerts
|

Resistive switching mechanism of ZnO/ZrO2-stacked resistive random access memory device annealed at 300 °C by sol–gel method with forming-free operation

Abstract: In this work, we used a sol-gel process to fabricate a ZnO-ZrO 2 -stacked resistive switching random access memory (ReRAM) device and investigated its switching mechanism. The Gibbs free energy in ZnO, which is higher than that in ZrO 2 , facilitates the oxidation and reduction reactions of filaments in the ZnO layer. The current-voltage (I-V) characteristics of the device revealed a forming-free operation because of nonlattice oxygen in the oxide layer. In addition, the device can operate under bipolar or uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…To overcome this issue, the concept of a bilayer structure RRAM has been investigated [9,20]. Jian et al [21] demonstrated that the ZnO/ZrO 2 bilayer structure RRAM device exhibited improved characteristics due to the Gibbs free energy difference between two SLs. Xue et al [22] reported on a WO x /ZnO bilayer RRAM device which showed good performance including an extremely low programming voltage, an attractive memory window, and improved device reliability.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this issue, the concept of a bilayer structure RRAM has been investigated [9,20]. Jian et al [21] demonstrated that the ZnO/ZrO 2 bilayer structure RRAM device exhibited improved characteristics due to the Gibbs free energy difference between two SLs. Xue et al [22] reported on a WO x /ZnO bilayer RRAM device which showed good performance including an extremely low programming voltage, an attractive memory window, and improved device reliability.…”
Section: Introductionmentioning
confidence: 99%
“…However, efforts are still needed to further improve the performance of RRAM devices based on TiO 2 films. It is known that the performance of various aspects of memristor devices can be improved by inserting switch layers of other metal oxides, 17,18 such as MnO/CeO 2 , 19 AlO x /HfO x , 20 ZnO/ZrO 2 , 21 rGO/ZnO, 22 MoS 2 /ZrO, 23 and TaO x /TiO 2 . 24 Dual-layer memory devices exhibit more significant switching performances than those of single-layer memory devices, such as reducing the switching voltage and enlarging the memory window.…”
Section: Introductionmentioning
confidence: 99%
“…For a RRAM device, poor cycling endurance and large resistive switching (RS) parameter fluctuations are the main problems for commercial industry application. A bilayer structure can improve the performance of the fabricated devices, and bilayer RRAM has been studied extensively, such as MnO/CeO 2 [17], AlO x /HfO x [18], ZnO/ZrO 2 [19], rGO/ZnO [20], CeO 2 /Nb:SrTiO 3 [21], MoS 2 /ZnO [22]. Compared with single-layer based memory devices, heterostructured and bilayer devices exhibit certain advantages, such as remarkable resistive switching performance, stable switching cycles, and data retention characteristics [23].…”
Section: Introductionmentioning
confidence: 99%